Strengthening Creative Economy through Communal Intellectual Property: Enriching Sustainable National Culture in Minority Ethnic Communities - Amelia Anggriany Siswoyo; Palacheta Subies Subianto; Qarissa Thirza Amanda (Greenation International Journal of Law and Social Sciences, 2026)
This research explores strategies to develop a creative economy based on Communal Intellectual Property in ethnic minority communities, focusing on the Indian Tamil community in Medan. This urgency arises from the lack of systematic inventory and legal protection, which leads to cultural loss and limited economic opportunities. Using a mixed-method approach, quantitative analysis examines the relationship between cultural behaviour, ecotourism, digital literacy, and commercialization literacy in strengthening communal culture. Qualitative methods, including focus group discussions and interviews with the Tamil community, complement the analysis. Results indicate that Communal Intellectual Property inventory and bundling with national cultural intellectual property could strengthen cultural sustainability and contribute to Indonesia’s creative economy. The study proposes a strategic model for integrating ethnic minority culture into the national framework of cultural enrichment and sustainable creative economy development.